Redefining stakeholder relationships in mega events: New Zealand Chinese and the Rugby World Cup. Issue 2 (3rd April 2017) - Lau, Chloe Kam Hong; Milne, Simon; Chi Fai Chui, Raymond
ABSTRACT: Through a proposed stakeholder framework with different participation modes, this study of the Chinese migrant community in Auckland explored the relationships around their participation in Rugby World Cup, namely, their awareness of the event and its link to event participation, economic links, identity, and national pride. Adopting a pre- and post-event approach, data from self-administered and online questionnaires were collected and examined using a multivariate analysis. A multidirectional participation effect was found for multicultural value, linkages, sense of identity and pride, business engagement, and recommending the country. Finally, stakeholder relationships were redefined by regrouping stakeholders in a mega sporting event.